The value of financial advice : an analysis of the investment performance of advised and non-advised individual investors - Allie, Jahangir (Department of Finance and Tax, 2016)
Financial advisors have long been considered a part of the financial market through the advice that they offer investors. Behavioural finance has demonstrated that individual investors do not always behave in a rational manner, unlike financial advisors who seem not be prone to the behavioural biases that individuals experience when investment decisions are made. Furthermore, financial advisors have greater access to information, financial analytical tools, as well as better education in financial markets compared to the average individual. Financial advisors are thus better equipped to assist individual investors and provide them with improved investment results. This study investigated the value added by financial advisors in the investment performance of advised individual investors as opposed to non-advised individuals. The study wanted to establish whether financially advised individuals showed greater return on investments than non-advised individuals. A sample of individual investors from a large South African investment house were analysed across the investment categories of an advised investor and a non-advised investor for a period of 10 years from 1 January 2005 to 31 December 2014. The data was analysed to draw conclusions on returns, trading behaviour, the risk profile of investors and the reasons for differences identified. The results indicated that there is no statistical difference between the returns generated between advised investors, non-advised investors and the fund invested over the period. There was a statistical difference between the number of trades entered into by advised and non-advised investors, with advised investors making statistically more trades than nonadvised investors. There was no significant difference between the risk profiles of the investors based on qualitative data. The results indicate that there is no significant additional benefit of utilising a financial advisor, after the initial decision of which fund to invest in has been made.